PENGARUH KINERJA KEUANGAN, KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP SUSTAINABILITY REPORT (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2010-2016) - Dinda Permatasari, 13.05.52.0104; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2017)
Sustainability report is a voluntary report to present corporate responsibility report on social, economic, environmental aspects. This study aims to examine the effect of profitability, liquidity, leverage, corporate activity, firm size, audit committee, board of directors, and independent board of commissioners towards sustainability report. The dependent variables in this study are sustainability report and the independent variables are profitability, liquidity, leverage, Company activity, company size, audit committee, board of directors, and independent board of commissioner. The population of this research is all mining industry companies listed on Indonesia Stock Exchange 2010-2016. The sample of this research is 40 companies. This research uses purposive sampling method. The disclosure indicator used in this study is the Global Reporting Initiative (GRI). The test results show that the liquidity and board of directors variables affect the sustainability report. Variable profitability, leverage, company activity, company size, audit committee, and independent board of commissioner have no effect on sustainability report.Keywords: Sustainability Report, Profitability, Liquidity, Leverage, Company Activity, Company Size, Audit Committee, Board of Directors, And Independent Board of Commissioners Again